Abraham, Wealth and Social Identity in Luke 16.19-31 - Groeningen, David van (2024)
This paper attempts to show Abraham as a social identity marker in Luke 16:19-31 (the parable of Lazarus and the Rich Man). The paper will use elements of social identity theory to analyse how Abraham functions as a social identity marker in this parable. After an introduction to elements of Social Identity Theory (SIT) that are relevant to the discussion, the paper will analyse how they relate to the characters in the pericope. Significantly, the paper will examine how a character might be expected to function in relation to Abraham as an exemplar, and will analyse how the characters in the parable have acted with reference to Abraham being an exemplar for the social group "Children of Abraham". A further theme of wealth disparity is put on display vividly in this parable, so the paper will also deal with how wealth and wealth inequality affect one’s social identity with reference to the group "Children of Abraham". The paper will end with a summary that ties all these ideas together.
Keywords: Abraham; Gospels; Luke; Social Identity Theory